Pengembangan Media Pembelajaran Baca Tulis Permulaan Berlandaskan Karakteristik Siswa - Dwi Yulianti; Supriadi Supriadi; Bambang Riadi; Munaris Munaris (JTP - Jurnal Teknologi Pendidikan, 2018)
The purpose of this study is to develop  preliminary reading and writing teaching media for the first (1st) grade elementary school students. The method used in this study is the Research and Development (R & D) approach. The results of the study were obtained from the first level of reading and writing teaching media, level 2 and level 3.  The results of learning media have undergone various validation tests and shown learning effectiveness. Content validation test results obtained mean rating 4.18, which means the media content is very valid. Language validation test results obtained 4.24 which means that the language of learning media is very good. Design validation results obtained 4.34, which means the teaching media design is very good. The effectiveness data shown that preliminary reading and writing teaching media has mean of 40.75 at 3â‰¤ RË‚4, which means that the preliminary reading and writing teaching media categorized as very effective in facilitating students to learn  how to read and how to write at the beginning.